Toxicity of Paraquat-Based Herbicide on Survival of African Catfish Clarias Gariepinus Fingerlings - S. O. Ikhuoriah; A. J. Ejomah; O. Uyi (Journal of Applied Sciences and Environmental Management, 2023)
Paraquat is a toxic chemical used as a broad spectrum, contact herbicide for aquatic weed control in many countries including Nigeria that has been implicated in many non-target effects in the environment. Clarias gariepinus, an important fish in aquaculture in Nigeria is also used as a bio-indicator species, as it plays an increasing important role in the monitoring of water pollution because it responds with great sensitivity to the changes in the aquatic environment. Therefore, this study investigated the effect of paraquat-based herbicide on the survival C. gariepinus fingerlings. Fingerlings were exposed to three concentrations of paraquat viz 3.44ml, 6.88ml and 13.75ml in tanks of 5 replicates. Percentage mortality was recorded after 24, 48 and 72-hour exposure. Paraquat exhibited a high degree of mortality against fingerlings, but the observed mortality was observed to be concentration and exposure time dependent. All concentrations used were below the manufacturer’s recommended concentration for aquatic weed control and they caused between 85 to 100% mortality after 72-hour exposure. Results from this study suggest that paraquat is highly toxic to C. gariepinus fingerlings and can therefore serve as reliable indicators of toxicity in environmental impact assessment programmes. Studies focusing on the effects of paraquat on aspects of the behaviour and physiology of juvenile stages of C. gariepinus are needed to fully understand the effects of this herbicide as results like this study show that paraquat can affect food supply (protein) and income to fish farmers.